Pengaruh Kompensasi Rugi Fiskal, Leverage, Capital Intensity, dan Transfer Pricing Terhadap Agresivitas Pajak: (Studi Pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Fauzan, Ilham; Asalam, Ardan Gani (eProceedings of Management, 2024)
Tax aggressiveness is a scheme to manipulate taxable income either legally (tax avoidance) or illegally (tax evasion).Companies engage in tax aggressiveness as it is seen as a way to reduce expenses and increase profits. This studyaims to examine the influence of tax loss compensation (KRF), leverage (LEV), capital intensity (CINT), and transferpricing (TP) on tax aggressiveness (AP) in energy sector companies listed on the Indonesia Stock Exchange (IDX)during the period 2019-2023, both collectively and partially. This research employs a quantitative approach with apurposive sampling technique, resulting in 10 companies observed over 5 years, totaling 50 samples. Panel dataregression analysis was used to analyze the data and the software used was Eviews version 12. The results show thatKRF, LEV, CINT, and TP collectively influence AP. However, partially KRF and LEV do not have a significant impacton AP, while CINT and TP have a significantly positive impact on AP. Keywords-fiscal loss compensation, leverage, capital intensity, transfer pricing and tax aggressiveness